POLYMORPHISMS OF INSULIN RECEPTOR SUBSTRATE 1 AS A RISK FACTOR FOR TYPE 2 DIABETES MELLITUS, OBESITY AND CHRONIC PANCREATITIS AMONG POPULATION OF TERNOPIL REGION - Hevko, U. P.; Marushchak, M. I. (International Journal of Medicine and Medical Research, 2021)
Background. The course of type 2 diabetes mellitus (T2DM), obesity and chronic pancreatitis (CP) in most cases is not isolated, so it requires broadening the knowledge about the pathogenetic links at their combined course. Despite significant advances in genome research, most of the genetic factors that cause development of T2DM are still unclear. Objective. The aim of the study was to establish the prevalence of IRS1 gene polymorphism in the patients with T2DM as well as obesity and CP. Methods. The study involved 34 patients with T2DM who were hospitalized in the endocrinology department of Ternopil University Hospital in 2019-2020 and 10 apparently healthy patients. Analysis of IRS1 gene polymorphism (SNP in the promoter region - rs2943640; gene localization 2q36.3) was performed on the basis of polymerase chain reaction data using specific primers. Results. It was found that the frequencies of the genotype responsible for C/A polymorphism of IRS1 gene in T2DM, T2DM with obesity and in the combined course of T2DM with obesity and CP did not deviate significantly from the Hardy-Weinberg equilibrium (p>0.05). The patients with combined course of T2DM, obesity and chronic pancreatitis experienced a probable influence of genotypes C/C and C/A of IRS1 gene on the development of the studied comorbidity (p<0.05), which is confirmed by a probable difference in the dominant model of IRS1 gene inheritance only when T2DM was combined with obesity and CP compared to the control group (p<0.001). Conclusions. The presence of the C allele in both homozygous and heterozygous states may increase the risk of T2DM comorbidity, obesity and CP in the population of Ternopil region.